2019
DOI: 10.5114/jcb.2019.87269
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of hepatic pancreatic ductal adenocarcinoma metastases with high-dose-rate image-guided interstitial brachytherapy: a single center experience

Abstract: PurposeTo evaluate the efficacy and safety of image-guided (computed tomography/magnetic resonance imaging – CT/MRI) high-dose-rate (HDR) interstitial brachytherapy (iBT) as a salvage maneuver for the treatment of hepatic metastases originating from hepatic pancreatic ductal adenocarcinoma (PDAC). PDAC metastases present a major and unresolved problem, and any surgical approach or local therapeutic intervention remains extremely controversial.Material and methodsA cumulative number of 45 hepatic PDAC metastase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 29 publications
(33 reference statements)
0
10
0
Order By: Relevance
“…Finally, 76 studies were identified, which provided a definition of OMD in PDAC and/or reported LCT of OMD ( Table 1 ). Most studies were retrospective ( n = 66, 87%), 2 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 ,…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, 76 studies were identified, which provided a definition of OMD in PDAC and/or reported LCT of OMD ( Table 1 ). Most studies were retrospective ( n = 66, 87%), 2 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 ,…”
Section: Resultsmentioning
confidence: 99%
“… 41 , 45 , 50 , 51 , 53 , 84 Thirty (40%) studies encompassed synchronous metastasis, 29 , 31 , 33 , 34 , 40 , 42 , 43 , 44 , 46 , 47 , 48 , 49 , 51 , 52 , 56 , 60 , 61 , 64 , 69 , 70 , 72 , 73 , 75 , 80 , 83 , 88 , 89 , 90 , 91 , 92 whereas 21 (28%) involved metachronous metastases 13 , 27 , 35 , 37 , 53 , 57 , 58 , 59 , 63 , 65 , 67 , 71 , 74 , 76 , 77 , 79 , 93 , 94 , 95 , 96 and 16 (21%) studies involved both synchronous and metachronous metastases. 2 , 14 , 30 , 32 , 36 , 38 , 39 , 54 …”
Section: Resultsmentioning
confidence: 99%
“…In a report of 16 patients with pancreatic cancer undergoing iBT for liver metastases, either disease progression under chemotherapy or discontinuation of chemotherapy due to drug-related toxicity were the two main reasons for referral to local treatment. This study reports a local tumor control of 87% and a median PFS of only 3.4 months [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Eighteen studies (7 primary, 11 metastasis) with 618 patients have been reported on receiving single-fraction treatment between 2004-2021 (Table 3). Seventeen studies were from Germany, and one was from Poland [25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42]. Single-fraction high-dose brachytherapy dose delivered ranged from 8 to 25 Gy.…”
Section: Livermentioning
confidence: 99%
“…G3 toxicity was reported in 3 patients with liver abscesses post-interstitial brachytherapy in a study done by Drewes et al . [ 29 ]. Other serious complications were noted, including post-interventional abdominal hemorrhage, pneumothorax, biliary abscess [ 41 ], and Gram-negative septicemia [ 38 ]; however, only a few cases were reported with such complications ( Table 3 ).…”
Section: Livermentioning
confidence: 99%